Callus induction of binahong leaves (Anredera cordifolia L.) for the development of traditional medicinal plant - Lili Sugiyarto; Paramita Cahyaningrum Kuswandi (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2014)
A plant that has a good prospect in the development and cultivation as medicinal plant is binahong (Anredera cordifolia L.). Secondary metabolites have been used as coloring substance, food coloring, and medicine. Callus induction using tissue culture has been used to produce secondary metabolite with a higher concentration than obtained directly from the plant. The aim of this research was to induce callus from the leaf of Binahong using various concentrations of Plant Growth Hormones in MS media. The method used in the propagation of callus used the leaf explant of binahong with Completely Randomized Design (CRD). The leaf explants were planted on MS media with different 2,4-D concentrations (1;2;3 ppm), 0,5ppm IBA+0,5ppm BAP; 0,5ppm IBA+1,0 ppm BAP; and 1,0 ppm IBA+0,5 ppm BAP, each with 15 repetitions. The result showed that the addition of 2,4-D (1 and 2 ppm) was able to induce callus from Binahong leaves on 3 and 5 days after planting, and also 10 days after planting in the controlled and combination treatment. In the 2,4-D media (1 and 2 pm), the callus produced were watery white and compact, while in the 3 ppm 2,4-D media the callus were white and friable. In the media with a combination of BAP and INA the callus were green and compact. The highest average diameter of the callus after 8 weeks in the 1 ppm 2,4-D media reached 2.07 cm followed by the 2 ppm and 3 ppm 2,4-D media producing a diameter of 1.8 cm. In the combination media (BAP and IBA), the callus diameter was less than 0.3 cm. The highest percentage of callus formed was in the media MS+1 ppm 2,4-D and a combination of MS +0,5ppm IBA+0,5ppm BAP that reached 100%. The lowest was found in the control (MS) which reached only 20%. The optimum growth of callus was at 3 weeks and after that it declined or stayed stagnant. The result of the analysis of variance (ANOVA) showed that there was no significant difference in the media used in this research. Key words: induction, binahong leaf, callus, plant growth